Malaysian budget 2022 : time for radical measures - Muhammed Abdul Khalid (2022)
The COVID-19 pandemic has posed serious challenges to Malaysia’s economic progress and potentially its social stability and upward mobility. The government’s eight stimulus packages have been too small to make a meaningful impact. Budget 2022 that will be tabled in the parliament in late October 2021 presents an opportunity to put in place radical measures.